Richmond Paper - The Deposits of Copper-Ores at Ducktown, Tenn. - J. F. Kemp (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1902)
PAGE Introductory Description of Deposits of this Type,.....244 Topography of the Ducktown Region,...247 Geology and Petrography,...248 The Mineralogy of the Ores and Gangue,..249 The older minerals : Amphibole, 250 ; Pyroxene, 250; Garnet, 251; Zoisite, 252; Calcite, 258 ; Quartz, 259 ; Apatite, 259 ; Rutile, 259. The Sulphides: Pyrite, 259; Zincblende, 259; Galena, 260; Pyrrho tite, 260; Chalcopyrite, 260. Later minerals, not belonging to the Gossan: Quartz, and certain sul phides, 261 ; Graphite, 261. The Formation of the Ore,...262 The Gossan Minerals,...........263 Bibliography,............265 Introductory Description of Deposits of this Type. Ore-bodies of more or less lenticular shape and lying parallel with the foliation of schists and slates form a group of